LUTS, alpha‐blockers and men's health. Issue 6 (November 2016) - Kirby, Roger
Abstract : With an increasing number of men presenting with lower urinary tract symptoms (LUTS), erectile dysfunction (ED) and the metabolic syndrome, Roger Kirby suggests that it is time to review current treatment approaches to avoid making some problems worse, and to try combinations of treatments that may be more beneficial for our patients.